STRUCTURALISM OF CHARACTER VALUES IN THE NOVEL â€œONE YEAR ACADEMICâ€ BY JUNIOR DANY WIBISONO - Syaiful Bahri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to determine the value theory of character education and structural theory. In line with the research objectives, this research uses qualitative research using descriptive methods. The data used in this study is a combination of intrinsic and extrinsic elements of literary works which include structural theory and the values of character education contained in the novel. The data source used in this research is the novel